FONDAPARINUX USAGE IN NON-ST-ELEVATION ACUTE CORONARY SYNDROME - G. V. Mardaryan; S. A. Abugov (Российский кардиологический журнал)
Anticoagulation treatment is a vital component of acute coronary syndrome treatment. Selection of the most efficient and safe drug for the acute coronary syndrome patients without ST elevation (NSTEACS) depends on the strategy of treatment and is in fact a difficult task. Fondaparinux (Arixtra) is a synthetic Xa factor clotting inhibitor, has showed its benefits in clinical studies, according to which it is included into clinical guidelines. Current review focuses on the main results and conclusions of the studies, and the place for fondaparinux in clinical practice is described